The Conspiracy of the Prince of Macchia and G.B. Vico - Pinton, Giorgio A. (Value Inquiry Book Series, 2013)
In September of 1701, events transpired in Naples that, through frequent retellings, became popularly known as "the conspiracy of the Prince of Macchia." Rapidly gaining fame, this apparently anonymous narrative was soon incorporated by different historians in their history of the transition years between the seventeenth and eighteenth centuries. But who was the initial bard or narrator, the town clerk or citizen who first gave testimony of this event by creating a Latin text of the story of the Prince of Macchia? Giambattista Vico was not among the claimants to the authorship of the fabulous story that changed the future of the Kingdom of Naples. Nevertheless, four scholars across the nineteenth and twentieth centuries were themselves convinced, and managed to convince the intellectual world as well, that Vico, then a young teacher of rhetoric at the University of Naples, was indeed the source of this original Latin narration of this oft retold Neapolitan history. This book provides the original Latin text with a parallel translation, as well as historical context and analysis of both the text's authorship history and the account itself.